1976
DOI: 10.1111/j.1471-4159.1976.tb02613.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diabetes, Insulin and Wallerian Degeneration on Leucine Metabolism of Isolated Rat Sciatic Nerves

Abstract: 14C0, production and I4C incorporation into proteins was studied in isolated rat sciatic nerves during incubation with 0.1 m~-[l-'~C]leucine. Rats were made diabetic with streptozotocin. Nerves from diabetic rats incubated with glucose oxidized more [14C]leucine than controls. This difference was abolished in the presence of insulin (1 mU/ml). The effects of diabetes and insulin on leucine oxidation could not be demonstrated in the absence of glucose. Insulin stimulated the incorporation of [14C] from leucine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Diabetic animals were included in the experiments only if the concentration of glucose in plasma was greater than 300 mg per 100 ml and if the animals either lost weight or gained less than 1 g per day. Previous studies from this laboratory [16] reported a weight gain of 6.75 _+ 0.28 g/day for 16 normal rats of the same strain and age.…”
Section: In Vivo Studiesmentioning
confidence: 81%
“…Diabetic animals were included in the experiments only if the concentration of glucose in plasma was greater than 300 mg per 100 ml and if the animals either lost weight or gained less than 1 g per day. Previous studies from this laboratory [16] reported a weight gain of 6.75 _+ 0.28 g/day for 16 normal rats of the same strain and age.…”
Section: In Vivo Studiesmentioning
confidence: 81%
“…In this regard, there is controversial information regarding actions of the hormone in vitro. Insulin has been reported to increase the rate of [3H]myo-inositol incorporation into phospholipids when added to segments of sciatic nerve (Hothersall and McLean,I979), to reverse the increased oxidation of [ ''C]leucine in diabetic rat nerves incubated with glucose (Buse et al, 1976), and to stimulate the incorporation of [ ''C]leucine into proteins of nerves from normal and diabetic rats (Buse et al, 1976;Spritz et al, 1976). On the other hand, composite glucose utilization in endoneurial preparations from rabbit sciatic nerves was found not to be subject to acute direct regulation by insulin at physiological concentrations (Greene and Winegrad, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…A marked decrease in incorporation of [ I4C]acetate occurs initially (Majno and Karnovsky, 1958;Rawlins and Smith, 197 1;Natarajan et al, 1982), but increases in incorporation of [32P]phosphate, [3H]glycerol, and [ ''C]choline have also been reported (Majno and Karnovsky, 1958;Natarajan et al, 1982). There are conflicting reports regarding metabolic alterations in protein synthesis during Wallerian degeneration; both increases (Rawlins and Smith, 1971;Buse et al, 1976;Pellegrino et al, 1986) and decreases (Porcellati, 1972;Bell et al, 1982) have been reported during the first week following nerve section. Invasion of the degenerating distal nerve stump by hematogenous cells Friede, 1984, 1986;Stoll and Muller, 1986;Muller and Minwegen, 1987) that participate in the eventual removal of degenerating myelin and other debris is clear, but This work was presented in part at the 19th Annual Meeting of Abbreviation used: SDS, sodium dodecyl sulfate.…”
mentioning
confidence: 99%